1999
DOI: 10.1097/00000542-199905000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ineffectiveness of Burst Suppression Therapy in Mitigating Perioperative Cerebrovascular Dysfunction 

Abstract: Electroencephalographic burst suppression surgery with propofol during cardiac valve replacement did not significantly reduce the incidence or severity of neurologic or neuropsychologic dysfunction. The authors' results suggest that neither cerebral metabolic suppression nor reduction in cerebral blood flow reliably provide neuroprotection during open heart surgery. Other therapeutic approaches must be evaluated to address this important medical problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(45 citation statements)
references
References 38 publications
0
43
0
2
Order By: Relevance
“…Nevertheless, the mechanisms and exact method of administering such cerebral protection strategy is still debatable [11].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the mechanisms and exact method of administering such cerebral protection strategy is still debatable [11].…”
Section: Discussionmentioning
confidence: 99%
“…Le propofol ne semble pas réduire les déficits neuropsychologiques après une chirurgie cardiaque valvulaire par rapport aux patients anesthésiés avec du sufentanil; toutefois, lorsqu'il est comparé à un régime de sédation par opiacés, le propofol a des résultats plus probants pour le traitement d'une pression intracrânienne élevée et résulte en un devenir neurologique semblable après un traumatisme crânien. 16,17 Une étude multicentrique portant sur des patients subissant une endartériectomie de la carotide sous anesthésie générale ou locale n'a pas révélé de différence dans l'incidence d'infarctus dans les 30 jours suivant la chirurgie. 18 Cette étude comporte plusieurs faiblesses, notamment le manque de puissance statistique, le peu de standardisation quant à l'anesthésique local utilisé et les niveaux de sédation variés du groupe anesthésique local; toutefois, les résultats réaffirment l'hypothèse selon laquelle une approche pharmacologique unique n'a que peu d'effet sur les nombreux événements pathologiques simultanés qui surviennent chez des patients présentant une variabilité parallèle à cause de maladies coexistantes.…”
Section: Resultsunclassified
“…Propofol does not appear to reduce neuropsychological deficits following cardiac valve surgery compared with sufentanil-anesthetized patients; however, when compared with an opioid-based sedative regimen, it shows more effective results in treating elevated intracranial pressure with a similar neurologic outcome following head injury. 16,17 A multicentre trial in patients undergoing carotid endarterectomy with general or local anesthesia revealed no difference in the occurrence of stroke within 30 days from the time of surgery. 18 Despite several limitations of that trial, including statistical underpowering, insufficient standardization of the local anesthetic used, and varying levels of sedation in the local anesthetic group, the data re-affirm the view that a single pharmacological approach can hardly affect the multiple simultaneous pathological events in patients with parallel variability of coexisting disease.…”
Section: Is There Clinical Evidence For Anesthetic Neuroprotection?mentioning
confidence: 99%
“…7 Unfortunately, there are very few human prospective randomized trials and most of those are in the context of various cardiac surgery protocols that offer a high incidence of measurable neuropsychological outcomes but are not necessarily appropriate to extrapolate to other clinical circumstances. 8,9 Other important issues are timing of drug administration, dose, durability of effect, and mechanism of action. The experimental literature is consistent in finding that anesthetics work best if given early in the ischemic period or, preferably, prophylactically.…”
mentioning
confidence: 99%
“…7 Malheureusement, il y a peu d'essais prospectifs randomisés chez l'humain et la majorité a été réalisée dans le contexte de divers protocoles de cardiochirurgie à forte incidence d'effets neuropsychologiques mesurables mais qui ne se prêtent pas nécessairement à une extrapolation à d'autres situations cliniques. 8,9 D'autres aspects importants concernent le moment choisi pour administrer le médicament, la dose, la durabilité de l'effet et le mécanisme d'action. Les données expérimentales montrent généralement que les anesthésiques agissent mieux s'ils sont administrés au début de l'ischémie ou, de préférence, de façon prophylactique.…”
unclassified